Digital Sociocracy: Navigating Governance Challenges in Southeast Asia - Munajat, MD Enjat; Irawati, Ira (Indonesian Association for Public Administration, 2025)
Digital sociocracy merges digital technology with sociocratic principles to improve participatory governance. This framework utilizes digital tools to enhance inclusivity, transparency, and efficiency across sectors such as urban management and energy systems. It advocates eight principles: Accountability, Equivalence, Consent, Transparency, Empiricism, Continuous Improvement, Digital, and Effectiveness to tackle governance challenges and support sustainable development. In Southeast Asia, the application of digital sociocracy encounters challenges such as digital literacy gaps and socioeconomic disparities. However, there are significant opportunities, as evidenced by initiatives that enhance governance quality and Sustainable Development Goals (SDGs). Singapore has emerged as a leader in adopting digital tools for participative governance, while other nations have shown varied progress and obstacles. This research formulates a quantitative model to evaluate the feasibility of digital sociocracy by employing indicators from global databases, such as the World Bank and SDG dashboards. These findings underscore the potential of digital sociocracy to bridge governance gaps, enhance citizen engagement, and promote equitable development. This study offers a strategic framework for policymakers to address the complexity of digital governance in Southeast Asia.